Analisis Penentuan Sektor Unggulan dan Klasifikasi Pertumbuhan Ekonomi Daerah di Kabupaten Temanggung Tahun 2011-2014 - Hariyanto, Sri (2016)
This study entitled "Determination of Sector Commodity Analysis and Classification of Regional Economic Growth in Temang- Year 2011-2014". The objective is to analyze the potential economic sectors seeded Temanggung district in 2011-2014. This research also classifies Temanggung regency economic growth in 2011-2014. The data used in this research is secondary data in the form of regional gross domestic product (GDP) and the Temanggung regency, Central Java province on the basis of current prices 2011-2014 were obtained from the Central Statistics Agency (BPS) and the Temanggung regency, Central Java province. The analysis tool used is the shift share Arcelus and Klassen typology. The results showed that the economy dominated Temanggung district four sectors, namely agriculture, trade, industry and the service sector-assistance services. In 2011-2012 Temanggung district of the leading sectors are agriculture, then next year 2012-2013 and 2013-2014 agricultural sector shifted the industrial sector, the services sector and trade sectors. Typology analysis Klassen indicates an economy the district of Temanggung when compared to Java province, the agricultural sector is the sector forward and grow, the services sector declined to a potential sector and still be expanded, the trade sector stabilized in potential sectors and still be expanded, and the industrial sector is still losing compete.